Issues of adaptation of European automobile emission standards in Ukraine - V.M. Ivasenko; I.V. Primisky (Технічна інженерія)
The article is devoted to the analysis of adaptation of European environmental standards for automobile emissions in Ukraine. Modern approaches to the rationing and control of automobile exhaust gases in the European Union countries are considered and compared with the current Ukrainian standards. Special attention is paid to the issues of harmonization of Ukrainian legislation with European environmental requirements in the context of reducing the negative impact of transport on the environment and public health. The composition of automobile exhaust gases, which include carbon dioxide (CO₂), carbon monoxide (CO), nitric oxide (NOₓ), hydrocarbons (CnHm), solid particles (PM) and sulfur dioxide (SO₂), is considered. Comparative data on the level of pollutants released during the combustion of gasoline and diesel fuel are presented. Special attention is paid to the harmful effects of these substances on human health and the ecosystem. European environmental standards known as «Euro» have been studied, ranging from the «Euro 1» Standard (introduced in 1993) to the modern «Euro VII», which will come into force in 2025. The methods used to reduce emissions are analyzed, in particular the use of catalytic converters, fuel injection systems, particulate filters, as well as the use of eco-friendly fuel. Special attention is paid to the analysis of the current regulations of Ukraine in the field of control of automobile emissions, in particular the standards DSTU 4276-04 and DSTU 4277-04, which regulate the permissible levels of dimension of diesel engines and the content of carbon monoxide and hydrocarbons in the exhaust gases of gasoline engines. The article analyzes the metrological support of automobile emission control devices, in particular gas analyzers and smoke meters. The principles of operation of these devices, their accuracy requirements, and main technical characteristics are described. The problems associated with the lack of uniform standards for certification of measuring instruments are identified, which complicates their application in Ukraine. It is noted that it is necessary to modernize Ukrainian environmental standards in accordance with EU requirements. It is proposed to develop new national standards regulating age levels, technical characteristics of measuring devices and methods of their application. They also stressed the importance of making changes to the current legislation to ensure environmental control of vehicles in accordance with modern European requirements.